Increased sugar-sweetened beverage consumption is associated with poorer dietary quality: A cross-sectional population-based study - Silva FONTES, Amanda; PALLOTTINI, Ana Carolina; dos Santos VIEIRA, Diva Aliete; Duarte BATISTA, Lais; de Mello FONTANELLI, Mariane; FISBERG, Regina Mara (Revista de Nutrição, 2023)
Objective To evaluate the association between sugar-sweetened beverages consumption and dietary quality in adolescents, adults, and older adults living in São Paulo, Brazil. Methods Data were drawn from a cross-sectional population-based study conducted in 2008 in a representative urban city sample involving 1494 consumers of sugar-sweetened beverages. Dietary intake was evaluated through two 24-Hour Dietary Recalls, and the usual sugar-sweetened beverages consumption was estimated using the Multiple Source Method. Dietary quality was evaluated using the Brazilian Healthy Eating Index – Revised. The association between total score of the revised index and components with sugar-sweetened beverages consumption tertiles was assessed using multiple linear regression models for each age group, considering the sample design. Results Regardless of age group, the increase of sugar-sweetened beverages consumption was associated with a decrease in the total Healthy Eating Index – Revised score and in the components “total fruit”; “whole fruit”; “meat, eggs and legumes”, and the “solid fat, alcohol and added sugar”. Conclusion The results of our study suggest that higher sugar-sweetened beverages consumption was associated with poorer dietary quality. Planning public health policies aimed at decreasing sugar-sweetened beverages consumption is essential to increase dietary quality and reduce the incidence of noncommunicable diseases.